The wolves of Willoughby Chase - Aiken, Joan, 1924-; Marriott, Pat. (New York, N.Y. : Dell Pub. Co., 1987)
Three children become involved in a series of adventures when left under the care of an evil detestable governess in the rural English manor of Willoughby Chase.
"A Yearling book."
Reprint. Originally published: c1962.
1020
Keywords: Runaway children -- Fiction